AKUImg: A database of cartilage images of Alkaptonuria patients. (July 2020) - Rossi, Alberto; Giacomini, Giorgia; Cicaloni, Vittoria; Galderisi, Silvia; Milella, Maria Serena; Bernini, Andrea; Millucci, Lia; Spiga, Ottavia; Bianchini, Monica; Santucci, Annalisa
Abstract: ApreciseKUre is a multi-purpose digital platform facilitating data collection, integration and analysis for patients affected by Alkaptonuria (AKU), an ultra-rare autosomal recessive genetic disease. We present an ApreciseKUre plugin, called AKUImg, dedicated to the storage and analysis of AKU histopathological slides, in order to create a Precision Medicine Ecosystem (PME), where images can be shared among registered researchers and clinicians to extend the AKU knowledge network. AKUImg includes a new set of AKU images taken from cartilage tissues acquired by means of a microscopic technique. The repository, in accordance to ethical policies, is publicly available after a registration request, to give to scientists the opportunity to study, investigate and compare such precious resources. AKUImg is also integrated with a preliminary but accurate predictive system able to discriminate the presence/absence of AKU by comparing histopatological affected/control images. The algorithm is based on a standard image processing approach, namely histogram comparison, resulting to be particularly effective in performing image classification, and constitutes a useful guide for non-AKU researchers and clinicians. Graphical abstract: Highlights: Development of the first Alkaptonuria-dedicated image repository. Release of an online tool to distinguish AKU/control cartilage slides for supporting researchers. Definition of an easily extendable method to be applied to other metabolic diseases.